Finishing Barn Cost Return Projection - Dhuyvetter, Kevin C.; Tokach, Mike D.; Dritz, Steve S. (My University, 2007)
This publication provides estimated cost and returns for a finishing barn.
MF2152_2007_10
Keywords: MF2152; Livestock; Economics; MF